Estudo da deterioração de marquises de concreto armado nas cidades de Uberlândia e Bambuí - Carmo, Marco Antônio do (2009)
In recent years the number of the constructed concrete marquees with pathological manifestations has grow in Brazil, and consequences have caused them to be structurally weak, which has generally lead to fatalities. As preventive action, it becomes necessary that the projects and construction thereof be improved in quality, that found pathological causes be corrected to prevent the repetition of the same errors, making sure that there is always a feedback of the system and all necessary maintenance is provided. By project analysis of geometric characteristics of the structure, visual inspection and detailed inspection with appropriate equipments, it can be detected existed anomalies and to made repairs and reinforcement of the structure, or even to indicate it demolition. This work represents the results obtained with the methodological implementation of the use of techniques inspection, norms and regulations that deal with constructed concrete skyways, with concern to guarantee their durability and, consequently, enhanced security for pedestrians. The studies had been carried through in the cities of Bambuí and Uberlândia. In the city of Uberlândia visual inspections of 54 marquees had been made, whereas in the city of Bambuí it became fulfilled visual inspection and inspection detailed in 10 of these structures, being used equipment of rebar locator, ultrasonic testing, measurer of corrosion potential of reinforcing bars and resistivity meter.